1997
DOI: 10.1007/s004420050154
|View full text |Cite
|
Sign up to set email alerts
|

Habitat linkages: the effect of intertidal saltmarshes and adjacent subtidal habitats on abundance, movement, and growth of an estuarine fish

Abstract: In this study we used pinfish (Lagodon rhomboides) in field experiments to examine linkages between intertidal saltmarsh and adjacent subtidal habitats. Pinfish are more than twice as abundant in intertidal marshes adjacent to seagrass beds than in those adjacent to the unvegetated subtidal bottom. Movement of pinfish between the marsh edge and the adjacent subtidal habitat was greater for fish captured in areas with both intertidal and subtidal vegetation than in those with intertidal vegetation and adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(107 citation statements)
references
References 20 publications
(32 reference statements)
0
106
1
Order By: Relevance
“…The landscape setting in which a reef is placed dictates the ability of many higher-level consumers to utilize it. For example, intertidal oyster reefs placed adjacent to salt marshes or adjacent to subtidal seagrass beds, rather than in isolation from other structured habitats, vary in their functioning by supporting different patterns of fish and crab utilization (Meyer et al 1996, Irlandi & Crawford 1997, Micheli & Peterson 1999, Grabowski 2002. Intertidal and subtidal oyster reefs are likely to differ in value to fish and mobile crustaceans largely because of the need to find alternative submerged refuge at low tide.…”
Section: Discussionmentioning
confidence: 99%
“…The landscape setting in which a reef is placed dictates the ability of many higher-level consumers to utilize it. For example, intertidal oyster reefs placed adjacent to salt marshes or adjacent to subtidal seagrass beds, rather than in isolation from other structured habitats, vary in their functioning by supporting different patterns of fish and crab utilization (Meyer et al 1996, Irlandi & Crawford 1997, Micheli & Peterson 1999, Grabowski 2002. Intertidal and subtidal oyster reefs are likely to differ in value to fish and mobile crustaceans largely because of the need to find alternative submerged refuge at low tide.…”
Section: Discussionmentioning
confidence: 99%
“…This movement pattern would maintain an animal's position in the shallowest water, thereby gaining refuge from aquatic predators and limiting energy expenditure. Regular tidal excursions may benefit growth in some species (Weisberg and Lotrich, 1982;Peterson and Turner, 1994;Irlandi and Crawford, 1997). Studies have shown a tidal periodicity in feeding, as evidenced by fuller guts on ebbing tides than on flooding tides (for fish see Kuipers, 1973;Rountree and Able, 1992; and for crustaceans see Ryer, 1987).…”
Section: 3l Tidal Excursionsmentioning
confidence: 99%
“…It is in terrestrial environments, however, that the quantification of landscape pattern and the study of the effect of pattern on ecological processes have made significant advances in understanding animal movement and persistence, the effects of disturbance, the importance of broad-scale environmental change and the design of resource management strategies (Turner, 1989;Saunders et al, 1991;Hobbs, 1994;Forman, 1995;Farina, 1998). Landscape ecology principles and tools are applicable throughout ecology and recent reviews have outlined the usefulness of a landscape ecology approach for the marine environment (Kneib, 1994;Robbins and Bell, 1994;Bell et al, 1997;Irlandi and Crawford, 1997;Eggleston, 1999). These reviews have rekindled interest in spatial pattern in the marine environment, with a number of researchers now applying and further developing concepts and analytical tools that have been used successfully in terrestrial landscape ecology.…”
Section: Spatial Hierarchymentioning
confidence: 99%
“…The proximity to alternative types of habitat has been shown to have important influences on the abundance and diversity of animals in other estuarine systems (e.g. Irlandi and Crawford, 1997).…”
Section: Sampling Designmentioning
confidence: 99%